Provenance Studies on Growth, Seed Yield and Quality of Chilli Genotypes (Capsicum annuum L.) - RAVI HUNJE,; B.S. VYAKARNAHAL,; R.C. JAGADEESH, (Seed Research, 2026)
Byadagi kaddi chilli variety exhibited significantly maximum seed yield and its components over Dyavanur local variety irrespective of localities. Byadagi kaddi variety recorded maximum plant height (92.21cm), number of primary (5.62) and secondary branches per plant (10.83), with early flowering (43.10 days) and maturity over Dyavanur local (82.91 cm, 4.70, 9.82, 46.40 days respectively) and also recorded significantly maximum fruit yield (1348 kg/ha), seed yield (495.42 kg/ha), fruit length (15.86 cm) and number of fruits per plant (109.50) over Dyavanur local (1227 kg, 405.90 kg, 12.60 cm, 91.08 respectively), where as Dyavanur local variety had maximum fruit girth (1.16cm), fruit weight (1.29g), number of seeds per fruit (81.50) and 100 seed weight (5.49g) compared to Byadagi kaddi variety (0.84 cm, 1.09 g, 66.62 and 4.85 g respectively). Dharwad location produced significantly maximum fruit yield, seed yield and seed quality parameters of chilli over Annigeri and Hanumanamatti locations. Byadagi kaddi variety grown at Dharwad location performed better with respect to growth and yield parameters compared to Dyavanur local variety.